Ácido cítrico e quitosana na conservação de lichias 'Bengal' - Guimarães, João Emmanuel Ribeiro [UNESP]; Morgado, Cristiane Maria Ascari [UNESP]; Galati, Vanessa Cury [UNESP]; Marques, Kelly Magalhães [UNESP]; Mattiuz, Ben-hur [UNESP] (Sociedade Brasileira de Fruticultura, 2013)
The aim of this study was to evaluate citric acid application with or without chitosan on the maintenance of the quality of litchi 'Bengal'. It was used litchi on mature maturation stage. After selection, fruits were immersed for one minute on the solution of citric acid and chitosan: [1]Control - without immersion; [2] citric acid 300g L-1, [3] citric acid 300 g L-1 + chitosan 0,3%, [4]citric acid 300 g L-1 + chitosan 0,6%, [5] citric acid 600 g L-1, [6] citric acid 600 g L-1 + chitosan 0,3%, [7] citric acid 600 g L-1 + chitosan 0,6%. Chitosan of low molecular weight and deacetylation degree of 75,58% (Sigma - Aldrich®) were used. After immersion, fruits were put to drain the excess of solution. Then, they were stored in cool chamber at 5ºC, previously sanitized, for 20 days. The experiment was conducted following a completely randomized design, with a factorial scheme composed by seven coating solutions and five sampling dates. Every five days were evaluated: loss of fresh mass of fruits; color; content of anthocyanins and the activity of peel enzymes polyphenoloxidase and peroxidase. It was verified that the solution of citric acid 600 g L-1, associated or not to chitosan, and the combination of chitosan 0,3% to 300 g L-1 of citric acid were the most efficient to maintain the quality of litchi 'Bengal' for 20 days at 5ºC.

Este trabalho teve como objetivo avaliar a aplicação de ácido cítrico em duas concentrações, associadas ou não à quitosana, na manutenção da qualidade de lichias 'Bengal'. Após a colheita e seleção, os frutos no estádio de maturação maduro foram imersos por 1 minuto nas seguintes soluções de ácido cítrico e de quitosana: [1] Testemunha - sem imersão; [2] ácido cítrico a 300 g L-1; [3] ácido cítrico a 300 g L-1 + 0,3% quitosana; [4] ácido cítrico a 300 g L-1 + 0,6% quitosana; [5] ácido cítrico a 600 g L-1; [6] ácido cítrico a 600 g L-1 + 0,3% quitosana; [7] ácido cítrico a 600 g L-1 + 0,6% quitosana. Após a imersão, os frutos foram colocados em gôndolas para escorrer o excesso de solução. Em seguida, foram armazenados em câmara fria, previamente higienizada, a 5ºC, durante 20 dias. O experimento foi conduzido seguindo um delineamento inteiramente casualizado, num esquema fatorial composto por sete soluções de recobrimento e cinco datas de amostragem. A cada cinco dias, foi avaliada a perda de massa fresca dos frutos, a coloração, o teor de antocianinas e a atividade das enzimas polifenoloxidase e peroxidase da casca. A solução de ácido cítrico a 600 g L-1, associada ou não à quitosana, e a combinação de quitosana 0,3% com 300 g L-1 de ácido cítrico foram as mais eficientes para a manutenção da cor avermelhada e a redução do escurecimento da casca de lichias 'Bengal' por 20 dias, a 5ºC.
Citric acid and chitosan in conservation of litchis 'Bengal'
Keywords: Litchi chinensis Sonn; Postharvest; Quality; darkening; Litchi chinensis Sonn.; Pós-colheita; qualidade; escurecimento